Analisis Kinerja Underwriter Dalam Menentukan Calon Peserta pada Produk Dana Pensiun: Studi Kasus Ajb Bumiputera 1912 Wilayah Medan - Imawanti, Yuki Dian; Lubis, Fauzi Arif; Suryani, Atika (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Insurance is a series of processes related to the supply of services needed by the community in quality. The magnitude of the influence of insurance on the sustainability of a company also makes the insurance process a good risk control. Without good handling, the impact on performance will be very large. This study uses qualitative research. Qualitative research is research that emphasizes the aspect of in-depth understanding of a problem rather than looking at the problem for generalization research. Underwriter performance assessment is carried out by the company leadership by considering the results of meetings of superiors, staff groups, committee decisions, field reviews and subordinates or colleagues. : a. Quality of work b. Work quantity c. Reliable d. Cooperative work Keywords: AJB Bumiputera 1912, Pension Fund and Underwriter